PENGARUH KONFLIK PERAN GANDA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT BODYWORKS HARUM SPA JALAN KAYU JATI NO. 2 PETITENGET KEROBOKAN - Ni Nyoman Kasi; I Made Hedy Wartana; I Ketut Eli Sumerta (Journal Research of Management, 2021)
Employee performance is something that needs to be considered in a company, because employee performance impacts in achieving goals. The problem raised in this study is whether dual role conflict (X1) affects the performance of employees (Y) at PT Bodyworks Harum Spa, whether work stress (X2) affects the performance of employees (Y) at PT Bodyworks Harum Spa, how much influence the dual role and work stress of the performance of the employees of PT Bodyworks Harum Spa and which independent variables have a dominant influence on the performance of employees at PT Bodyworks Harum Spa. The population in this study amounted to 109 people, this study uses the population as a sample. The analysis technique used is descriptive analysis, data quality test, classic assumption test, linear regression analysis, t-test analysis. The analysis shows the regression model Y = 48,663 - 617 (X1) - 538 (X2). The conclusion obtained is that multiple role conflict (X1) partially has a negative and significant effect on employee performance (Y) at PT Bodyworks Harum Spa as shown by the negative coefficient b1X1. Work stress partially has a negative and significant effect on employee performance (Y) at PT Bodyworks Harum Spa as indicated by the negative coefficient b2X2 regression coefficient. The magnitude of the influence of multiple roles and work stress on the performance of employees of PT Bodyworks Harum Spa by 40.8% and the remaining 59.2% is influenced by variables not examined in this study. The independent variable that has a dominant influence on employee performance can be seen in the value of Standardized Coefficients Beta is a dual role variable (X1) that is equal to - 369 while the work stress variable (X2) is - 341.